RETOS Y OPORTUNIDADES DEL SOCIAL MEDIA EN LA ORGANIZACIÓN CONTEMPORÁNEA - Salvador Madrigal Moreno; Flor Madrigal Moreno; Cuauhtémoc Guerrero Dávalos (European Scientific Journal, ESJ, 2015)
Social media is a reality in the information society. This research focuses in how the development of the information society and the presence of the Information and Communications Technology (ICT) provide the acceptable environment for the deployment of organizational communication and social media marketing. It describes the particularities of social media as a growing phenomenon of great social appropriation that, thanks to the Internet, has caused that the modern organization contemplates implementing social media to its benefit. The purpose of this paper is to contextualize the use of social media and establish the challenges and opportunities of implement communication and social media marketing strategies in the organization. The present study confirms that the information society has established the conditions to properly implement social media marketing and the risks are considerably lower than the opportunities.